Capacitación a los contadores para cargos ejecutivos y gerenciales en Colombia (2021)
Lately it can be evidenced that the senior management and executive positions are not mostly occupied by graduates of the public accounting faculty, but the high demands of these positions are occupied by graduates of different faculties, besides to the fact that the public accountant is known more as a consultant or auditor and as a result reflecting an absence of the union in these large positions, what is intended with the development of this work is to be able to demonstrate that public accountants could obtain the management competencies and skills for the occupation of these positions.